2013
DOI: 10.4067/s0718-95162013005000076
|View full text |Cite
|
Sign up to set email alerts
|

Oxytetracycline on functions and structure of soil microbial community

Abstract: Effects of oxytetracycline (OTC) on soil enzyme activity and structural diversity of soil microbial communities were investigated. The low and moderate OTC inputs of less than 15 mg/kg enhanced microbial growth and increased the total and bacterial and fungal biomasses in the receiving soils. The antibiotic toxicity of OTC although targeted the bacteria in the soils proportionally resulted in greater harmed against the soil fungi than the bacteria and the Gramnegative bacteria fared significantly better than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
3
25
1
1
Order By: Relevance
“…The influence of VAs on total bacteria and total fungi PLFA markers and their ratio appears to be dependent on a number of variables, including the soil, VA, and manure properties and concentrations. Chen et al (2013) reported increased bacteria and fungi PLFA markers in loam soil at OTC concentrations ≤15 mg kg -1 . However, at OTC concentrations >15 mg kg -1 , fungi were adversely affected to a greater extent than bacteria, and Gram-positive bacteria were reduced to a greater extent than Gram-negative bacteria.…”
Section: Phospholipid Fatty Acidsmentioning
confidence: 94%
“…The influence of VAs on total bacteria and total fungi PLFA markers and their ratio appears to be dependent on a number of variables, including the soil, VA, and manure properties and concentrations. Chen et al (2013) reported increased bacteria and fungi PLFA markers in loam soil at OTC concentrations ≤15 mg kg -1 . However, at OTC concentrations >15 mg kg -1 , fungi were adversely affected to a greater extent than bacteria, and Gram-positive bacteria were reduced to a greater extent than Gram-negative bacteria.…”
Section: Phospholipid Fatty Acidsmentioning
confidence: 94%
“…Many studies have revealed that antibiotics affect the number of different groups of microorganisms (Pinna et al, 2012 ; Akimenko et al, 2015 ; Xu et al, 2016 ), the structural and genetic diversity of microorganisms and the overall microbial activity (Demoling et al, 2009 ; Cui et al, 2013 ; Liu et al, 2014 ; Reichel et al, 2014a , b ; Cycoń et al, 2016a ; Xu et al, 2016 ). Moreover, the impact of antibiotics on the enzyme activities, carbon mineralization, and nitrogen cycling has been proven (Liu et al, 2009 ; Kotzerke et al, 2011 ; Rosendahl et al, 2012 ; Chen et al, 2013 ; Ma et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The initial concentration of OTC added to the soil at 150 mg kg −1 was selected on the basis of a literature search. The other authors used 1 to 300 mg kg −1 of tetracycline in their studies (Chen et al 2013;Molaei et al 2017;Duan et al 2017). During the 30-day incubation of soil contaminated with antibiotic, the concentration of OTC content was measured by liquid chromatography.…”
Section: Resultsmentioning
confidence: 99%